การคิดนวัตกรรมด้วยหลักการทรงงานตามหลักปรัชญาหลังนวยุค - Nopchalermroj, Chairoj (Journal of Community Development Research (Humanities and Social Sciences); Vol 15 No 2 (2022): April - June 2022DO - 10.14456/jcdr-hs.2022.19, 2022)
งานวิจัยนี้เป็นการวิจัยเชิงคุณภาพ มีวัตถุประสงค์เพื่อวิเคราะห์การคิดนวัตกรรมด้วยหลักการทรงงานตามหลักปรัชญาหลังนวยุค ผลการวิจัย พบว่า การคิดนวัตกรรมด้วยหลักการทรงงานตามหลักปรัชญาหลังนวยุคเริ่มต้นจากการตั้งคำถามว่า คิดเพื่อใคร คำตอบอยู่ท้ายพระปฐมบรมราชโองการที่ว่า “...เพื่อประโยชน์สุขของมหาชนชาวสยาม” เมื่อนำมาคิดนวัตกรรมจึงต้องคำนึงถึงประโยชน์สุขส่วนรวมเป็นสำคัญเพื่อการพัฒนาคุณภาพชีวิตตามเป้าหมายของปรัชญาหลังนวยุค ทฤษฎีที่สำคัญต่อการคิดนวัตกรรม คือ ทฤษฎี SAPAE เริ่มต้นจาก S = Survey/การสำรวจ ได้แก่ การสำรวจความต้องการหรือปัญหาของประชาชน A = Analysis/การวิเคราะห์ ได้แก่ การนำข้อมูลที่ได้มาทำการวิเคราะห์ เพื่อจำแนกและคัดเอาสิ่งที่จำเป็นที่สุดออกมา เพื่อการต่อยอดให้เหมาะสมกับการสภาพปัญหาที่ต้องการแก้ เทคนิคการคิดวิเคราะห์ในขั้นตอนที่สอง เริ่มต้นจากการตั้งคำถามด้วยคำว่า “ทำไม” และ “ได้หรือไม่” เพื่อกระตุ้นให้คิดสิ่งใหม่ๆ หรือพัฒนาสิ่งใหม่เพื่อต่อยอดสิ่งเก่าให้ดีกว่าเดิม P = Planning/การวางแผน ได้แก่ การเริ่มต้นจากการไม่มีแผน เพื่อกลับมาอยู่กับการสังเกตจนได้ข้อมูลที่น่าเชื่อถือที่สุดที่เกิดขึ้น ณ เวลาปัจจุบัน เมื่อเราสามารถเป็นนักสังเกตปรากฏการณ์ที่เกิดขึ้นจนเข้าใจถึงสภาพปัญหาได้อย่างดีแล้ว จึงเริ่มวางแผนโดยคำนึงถึงการมีส่วนร่วมในทุกภาคส่วนที่เกี่ยวข้อง A = Action/การปฏิบัติ ได้แก่ การเริ่มดำเนินงานตามโครงการ โดยการทดสอบในแต่ละขั้นตอน E = Evaluation/การประเมินผล ได้แก่ การทดสอบประสิทธิภาพ เพื่อดูประสิทธิผลที่เกิดขึ้น ทั้งในส่วนที่เป็นเครื่องมือเครื่องใช้หรือรูปแบบการบริการ เมื่อทดสอบเป็นที่แน่ใจแล้วก็จะได้ข้อสรุปสำหรับเป็นแนวทางในการปฏิบัติต่อไป คำสำคัญ: นวัตกรรม  หลักการทรงงาน  ปรัชญาหลังนวยุค           This research is a qualitative research. The objective is to analyze innovative thinking with the royal working principles of King Bhumibol Adulyadej according to the postmodern philosophy. The results of the research indicated that innovative thinking with the philosophy of post-modern began by asking the question of whom is this principle thinking for? The answer is at the end of the Royal Command that “We shall reign in righteousness for the benefits and happiness of Siamese people”. When it comes to thinking of innovation, the public benefit must be taken into account for the development of quality of life according to the goals of the post-modern philosophy. The theory that is important to innovative thinking is SAPAE: S = Surveys, such as a survey of needs or problems of the people. A = Analysis, such as analyzing the obtained data in order to classify and select what is most necessary to extend it to be suitable for the problem condition to be solved. Analyzing is the next step after asking questions with the words “Why?” and “Possible or not?” to urge the better way of thinking or development from the old ways. P = Planning, for example, starting from the absence of a plan to return to the observation until obtaining the most reliable information that occurs at the present time. When we are able to become observers of phenomena that occur and understand the problem condition, we begin planning by considering participation in all relevant sectors in order. A = Action, such as, starting the implementation of the project by testing each step. E = Evaluation, such as, testing of evaluation to see effectiveness of either tools or service models. Once we feel sure of the test, we can draw the conclusions for further actions. Keywords: Innovation, Working Principles of King Bhumibol Adulyadej, Postmodern Philosophy